2017
DOI: 10.1371/journal.pone.0188442
|View full text |Cite
|
Sign up to set email alerts
|

Dronedarone produces early regression of myocardial remodelling in structural heart disease

Abstract: Background and aimsLeft ventricular hypertrophy (LVH) in hypertension is associated with a greater risk of sustained supraventricular/atrial arrhythmias. Dronedarone is an antiarrhythmic agent that was recently approved for the treatment of atrial fibrillation. However, its effect on early regression of LVH has not been reported. We tested the hypothesis that short-term administration of dronedarone induces early regression of LVH in spontaneously hypertensive rats (SHRs).MethodsTen-month-old male SHRs were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(56 reference statements)
2
13
0
Order By: Relevance
“…Our results are consistent with other studies that describe a decrease in blood pressure and heart rate associated with the administration of this drug [11]. Our group has previously demonstrated that dronedarone produces a regression of LVH in hypertensive rats after two weeks of treatment [14]. However, the impact of this drug on the remodeling of the elastic arteries (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with other studies that describe a decrease in blood pressure and heart rate associated with the administration of this drug [11]. Our group has previously demonstrated that dronedarone produces a regression of LVH in hypertensive rats after two weeks of treatment [14]. However, the impact of this drug on the remodeling of the elastic arteries (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Dronedarone produces a reduction in the risk of stroke [10] and acute coronary syndrome [11] that may be related to reduced heart rate and arterial blood pressure [12,13]. Our group has previously demonstrated that dronedarone produces regression of left ventricular hypertrophy (LVH) in hypertensive rats after two weeks of treatment (resulting in reduced left ventricular mass, changes in the cardiomyocytes and collagen of the left ventricle, and an improvement in cardiac metabolism) [14]. However, the impact of this drug on vascular remodeling has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Functional and structural alterations of the coronary circulation have been well documented in left ventricular hypertrophy [1]. In a preclinical study, we show that short-term treatment (two weeks) with dronedarone has the potential to reverse the left ventricular hypertrophy induced by arterial hypertension in the SHR model of compensated ventricular hypertrophy [10]. In this context, we found it of interest to assess the impact of dronedarone in attenuating intramyocardial artery remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Dronedarone reduced the incidence of hospitalization due to cardiovascular events or death in patients with atrial fibrillation [7, 8]; however it is avoided in patients with unstable chronic heart failure [9]. In a preclinical study, we previously analyzed early regression of left ventricular hypertrophy following short-term use of antiarrhythmic agents and we found that dronedarone produces regression of left ventricular hypertrophy after two weeks of treatment [10]. However, its effect on intramyocardial artery remodeling has not been analyzed to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may worsen the clinical status of hemodynamically unstable patients or those with moderate to severe ventricular dysfunction ( Kober et al, 2008 ). Our group previously demonstrated that dronedarone produced regression of LVH after only 14 days of treatment in a preclinical study ( Quintana-Villamandos et al, 2017 ). In the present study, we aim to analyze the possible mechanisms responsible for this effect.…”
Section: Introductionmentioning
confidence: 98%